Spanish “Politically Correct” Movement: Reasons for Failure - María Isabel Maldonado García (Journal of Political Studies, 2015)
The controversy about sexism in the Spanish language is not a new phenomenon. However, in 2010 it generated a "politically correct" movement propelled by a few political parties by which various non-academic institutions had created guidelines for a "non-sexist" Spanish language and several universities joined in this enterprise. Most non-sexist proposals included splits in order to include both genders and other initiatives in order to cancel, reduce or perhaps counteract those "sexist" language elements. Ignacio Bosque from the Royal Academy of Spanish Language’s analysis, published in El País on 4 March of 2012, supported by more than eight hundred Spanish linguists, countered this movement and to date it has not been refuted from a linguistic point of view. In this study, the effort, as well as Ignacio Bosque’s document will be analyzed from a logical as well as from a linguistic point of view. The reasons for the failure of the movement will be stated as well.